21% versus 79%: Explaining philosophy's gender disparities with stereotyping and identification. (2nd January 2018) - Ma, Debbie; Webster, Clennie; Tachibe, Nanae; Gressis, Robert
Abstract: This study tests the hypothesis that the perception of philosophy as a male-oriented discipline contributes to the pronounced gender disparity within the field. To assess the hypothesis, we determined the extent to which individuals view philosophy as masculine, and whether individual differences in this correspond with greater identification with philosophy. We also tested whether identification with philosophy correlated to interest in it. We discovered, first, that the more women view philosophy as masculine, the less they identify with it, and second, that the less women identify with philosophy, the less they want to major in it. Interestingly, this result does not hold for men—their viewing philosophy as masculine does not correspond to their identification with it, nor does it correlate with their likelihood of majoring in it. We also discovered that the typical student does not have a preconceived notion of philosophy as masculine; this suggests that they come to view philosophy as masculine the more they do it, which in turn supports the possibility that teaching the discipline differently may prevent students from conceiving of philosophy as masculine, thus allowing a path to reducing the gender disparity.